Accuracy of 18-F FDG PET/CT to detect bone marrow clearance in patients with peripheral T-cell lymphoma – tissue remains the issue. Issue 10 (3rd October 2017) - Pham, Anthony Q.; Broski, Stephen M.; Habermann, Thomas M.; Jevremovic, Dragan; Wiseman, Gregory A.; Feldman, Andrew L.; Maurer, Matthew J.; Ristow, Kay M.; Witzig, Thomas E.
Abstract: Staging of peripheral T-cell non-Hodgkin lymphoma (PTCL) is determined by 18-F FDG PET scan and bone marrow biopsy. This study addressed the accuracy of PET at detecting bone marrow (BM) involvement at restaging in patients with known involvement pretreatment. We identified patients with biopsy proven BM PTCL at diagnosis and concomitant BM and PET at the end of therapy. Pre-treatment PET demonstrated 50% (8/16) had a false-negative PET scan of the BM. After induction, repeat biopsy revealed 62.5% (10/16) with BM involvement. Of these 10, two had a positive PET; eight were false negative by PET. Of the six patients with a negative posttherapy BM biopsy, four were PET negative and two false positive. The sensitivity of PET at end of treatment was 20% (2/10) with a specificity of 66.7% (4/6). PET/CT is not an accurate predictor of BM involvement in patients with known PTCL in the marrow.